Impact of congenital heart disease on brain development in newborn infants - Moustafa M Abdel Raheem; Walid A Mohamed (Wolters Kluwer Medknow Publications, 2012)
Objective: To assess brain development and brain injury in neonates with cyanotic and acyanotic congenital heart disease (CHD). Methods: The study included 52 term infants with CHD who were divided into two groups: Cyanotic (n=21) and acyanotic (n=31). Fifteen healthy neonates of matched age and sex were enrolled in the study as controls. Three-dimensional proton magnetic resonance spectroscopic imaging and diffusion tensor imaging were used to assess brain development and injury. We calculated the ratio of N-acetylaspartate (NAA) to choline (which increases with maturation), average diffusivity (which decreases with maturation), fractional anisotropy of white matter (which increases with maturation), and the ratio of lactate to choline (which increases with brain injury). Results: As compared with control neonates, those with CHD had significant decrease in NAA/choline ratio (P<0.001), significant increase in lactate/choline ratio (P<0.0001), significant increase in average diffusivity (P<0.0001), and significant decrease of white matter fractional anisotropy (P<0.001). Neonates with cyanotic CHD had significant less brain development and more brain injury than those with acyanotic CHD (P<0.05). Conclusions: Newborn infants with cyanotic and acyanotic CHD are at high risk of brain injury and impaired brain maturity.